1975
DOI: 10.1136/gut.16.7.514
|View full text |Cite
|
Sign up to set email alerts
|

Electronmicroscopic observations on the effects of orally administered aspirin and aspirin-bicarbonate mixtures on the development of gastric mucosal damage in the rat.

Abstract: SUMMARYThe effects of administering a single dose of (200 mg to 50 mg/kg body weight) aspirin or an equimolar mixture of aspirin (200 mg/kg body wt) with sodium bicarbonate on the fine structure of the rat gastric mucosa were investigated in order to establish the role of particles of the drug in the development of gastric damage. The sequence of cellular events involved in the development of a lesion and the influence of short-term starvation were also investigated. Aspirin-bicarbonate solutions produced much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1975
1975
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…In this respect the rat is a very useful species to study the development of gastric mucosal damage as the damage is obviously confined to the acid-secreting area of the stomach. This indicates that the property of acidity and the existence of a susceptible tissue, well known factors in the development of aspirininduced damage [11,13], are also major factors in the development of damage by aspirin + stress.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In this respect the rat is a very useful species to study the development of gastric mucosal damage as the damage is obviously confined to the acid-secreting area of the stomach. This indicates that the property of acidity and the existence of a susceptible tissue, well known factors in the development of aspirininduced damage [11,13], are also major factors in the development of damage by aspirin + stress.…”
Section: Resultsmentioning
confidence: 96%
“…The animals were dosed orally with aspirin B.P. or other non-steroidal anti-inflammatory or analgesic drugs (as listed in Table 3) according to procedure employed previously [11]. Control animals were dosed with 1 ml H20 and the drugs were given as 1 ml suspensions in H20.…”
Section: (A) Studies In Ratsmentioning
confidence: 99%
“…The necrotic foci were typically yellow and were found in the wall of the jejunum and ileum. It is interesting that gastric lesions were not apparent, since all four compounds have been shown to produce gastric toxicity experimentally (6,8). The fact that food was made available shortly after drug administration and the possibility that the stomachs may not have been completely empty at the time ofdrug administration may have been causative factors.…”
Section: Introductionmentioning
confidence: 99%
“…ASA is efficacious (3) and inexpensive, but it also has liabilities. These liabilities, including gastrointestinal intolerance and irritation (6,8), have led to the development of the numerous nonsteroidal anti-inflammatory drugs (NSAID) that are either available, or under evaluation, today. However, many of these M A I D also have liabilities, including gastrointestinal irritation.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on the morphological and histochemical changes in the gastric mucosa associated with the prog ress of experimental gastric ulcers [4,6,[9][10][11]. However, little work has been done on the biochemical aspects of these changes.…”
mentioning
confidence: 99%